Steep uphill cycling using repeated transitions between seated and standing positions results in a lower blood-lactate concentration than continuous use of either seated or standing position - Carlsson, Magnus; Lindblom, Oliver; Carlsson, Tomas (Frontiers in Sports and Active Living, 2024)
This study investigated whether repeated transitions between seated and standing positions has a different physiological response compared to continuous use of either seated position or standing position during steep uphill cycling among elite cyclists. Ten elite male cyclists completed three 5-min treadmill cycling tests at an inclination of 6.8° with constant individual-based speed resulting in a work intensity close to the aerobic threshold. During the first and third test, the participants used standing position (ST test) and seated position (SE test) or vice versa, whereas in the second test, they made repeated transitions between standing and seated positions every 10 seconds (RT test). The last 2 min of each test was used to measure the mean values of oxygen uptake (V ̇O2) and respiratory exchange ratio, which were used to calculate the metabolic rate (MR) and gross efficiency (GE). Additionally, the blood-lactate concentration before and after (Lapost) each test was determined. One-way repeated measures ANOVA was used to determine the effect of cycling position on the physiological response. No significant differences between tests were observed for the variables related to aerobic energy expenditure (i.e. V ̇O2, MR and GE), whereas the RT test was associated with a significantly lower Lapost compared to the ST and SE tests. Steep uphill cycling, at an intensity close to the aerobic threshold, with repeated transitions between standing and seated positions, did not have a higher oxygen consumption; instead, the blood-lactate concentration was lower during the RT test compared to that under continuous use of either seated or standing position.